Communication from the executive of the Commonwealth, returning the nomination of Francis I. Thomas, with accompanying documents (LLMC-digital (Series), 1861)
Governor John Letcher's letter of transmittal and various documents in response to the Convention request that the governor withdraw the nomination of Francis I. Thomas to the rank of a colonel. Included was a letter of support from (apparently) a delegate of the Convention, as well as a letter from Thomas, seeking information and an opportunity to defend himself from this "disgrace."